Newly discovered Aurignacian engraved blocks from Abri Cellier: History, context and dating. (30th December 2018) - White, Randall; Bourrillon, Raphaëlle; Mensan, Romain; Clark, Amy; Chiotti, Laurent; Higham, Thomas; Ranlett, Sarah; Tartar, Elise; Morala, André; Soulier, Marie-Cécile
Abstract: The rich record of Aurignacian graphic arts from sites in the Vézère Valley of SW France holds a key place in our understanding of systems of representation in the European Early Upper Paleolithic. One of the main sites yielding representational objects is Abri Cellier, which has long been on the short-list of major art-bearing sites attributed to the European Aurignacian. Collie's 1927 excavations yielded 15 engraved and/or pierced limestone blocks that have served as a key point of reference for the study of Aurignacian art in SW France. As part of a broader re-excavation of key Aurignacian sites in the Vézère Valley, we returned to Abri Cellier in 2014, with detailed archives in hand, in the hopes of finding intact deposits that would allow a better understanding of the archaeological sequence at the site and its relationship to other Aurignacian sites in the so-called "classic zone." While disappointingly little is left of the site, the 2014 season allowed the addition of 16 new engraved, painted or pierced blocks to the 15 already known from the 1927 excavations. We present here a brief history of excavations at the site, a stratigraphic analysis, an overview of archaeological materials recovered, a series of 14C ultrafiltration dates, a brief discussion of the peculiar characteristics of Aurignacian block art in SW France, a detailed analysis of the engraved surfaces of the blocks discovered in 1927 and in 2014 and finally a comparison of the newly-revised Cellier block assemblage with those from other Aurignacian sites in the Vézère.